2010
DOI: 10.3109/09687688.2010.507788
|View full text |Cite
|
Sign up to set email alerts
|

Light-sensitive lipid-based nanoparticles for drug delivery: design principles and future considerations for biological applications

Abstract: Radiation-based therapies aided by nanoparticles have been developed since decades, and can be primarily categorized into two main platforms. First, delivery of payload of photo-reactive drugs (photosensitizers) using the conventional nanoparticles, and second, design and development of photo-triggerable nanoparticles (primarily liposomes) to attain light-assisted on-demand drug delivery. The main focus of this review is to provide an update of the history, current status and future applications of photo-trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
115
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 126 publications
1
115
0
Order By: Relevance
“…Photosensitizers, when incorporated into nanoparticles, can sometimes be used to trigger release the encapsulated contents upon NIR irradiation 211, 212, 213. It has been demonstrated that liposomes incorporating porphyrin‐phospholipid (PoP) can be permeabilized by NIR light, releasing variable cargos such as Dox, calcein, sulforhodamine B, and gentamicin 208.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
See 1 more Smart Citation
“…Photosensitizers, when incorporated into nanoparticles, can sometimes be used to trigger release the encapsulated contents upon NIR irradiation 211, 212, 213. It has been demonstrated that liposomes incorporating porphyrin‐phospholipid (PoP) can be permeabilized by NIR light, releasing variable cargos such as Dox, calcein, sulforhodamine B, and gentamicin 208.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…Most nanoparticles currently being used are successful by reducing side‐effects or as a means to solubilize hydrophobic drugs to induce fewer side effects 24. However, there has been significant preclinical work focused on developing new strategies for improving the delivery and efficacy of drugs using nanoparticles that are responsive to external stimuli such as heat,25, 26, 27, 28 light,29, 30, 31, 32, 33 ultrasound34 or tumor environment factors such as lower pH35, 36, 37, 38 or expression of certain enzymes 39, 40…”
Section: Introductionmentioning
confidence: 99%
“…Successful disruption of the vesicles could be demonstrated after irradiation with UV-light by electron microscopy and dynamic lights scattering data. The design of photocleavable liposomes for drug delivery using different photolabile groups has been reported in several publications (15,16) . Dvir et al presented a simple proof of concept by carboxylated polystyrene nanoparticles labeled with the unspecifi c amino acid sequence YIGSR, which adheres to β 1 integrins present on most cell surfaces (4,17) .…”
Section: Application Of Light In Nanomedicine Light For Triggered Relmentioning
confidence: 99%
“…The caging groups are either covalently attached to the phosphate backbone or terminal phosphates or on the nucleotide bases to inhibit the further process of RNA induced silencing (Figure 2). The fi rst report of caged siRNA has been described by Shah et al using 1-(4, 5-dimethoxy-2-nitrophenyl)ethyl (DMNPE) attached to the phosphate backbone which only showed a 3 % caging effi ciency (15,16,24) . Caging of guanosine and thymidin bases by attaching 2-(2-nitrophenyl)propy (NPP) groups has been reported by Mikat and Heckel (25) .…”
Section: Light Induced Gene Expression and Control Of Gene Silencingmentioning
confidence: 99%
“…The use of nanocarriers that can be remotely disassembled to release RA with spatial and temporal resolution are of high therapeutic value [15,16]. Even if LR-NP distribute to other tissues, RA will be released only upon light stimulation, bypassing possible side effects [17].…”
Section: Introductionmentioning
confidence: 99%